การเตรียมความพร้อมการเกษียณอายุของข้าราชการครูในจังหวัดตรัง - ปรารถนา หลีกภัย (มหาวิทยาลัยสงขลานครินทร์, 2023)
This research aimed to study the retirement preparation of teachers in Trang Province and to compare their retirement preparation with the demographic factors. This study also intended to explore factors affecting the retirement preparation of teachers in Trang Province. A quantitative research approach was employed. The sample groups of this study were teachers who work in the Primary Educational Service Area Office Trang 1 and the Primary Educational Service Area Office Trang 2; and teachers who work in the Secondary Educational Service Area Office Trang 13. In total, 400 teachers were recruited. The questionnaire was the main instrument for collecting the data. The descriptive statistics, namely, frequency, percentage, mean, and standard deviation were used to describe the characteristics of the data set. In addition, the T-test, the F-test, and the multiple regression were applied to examine the factors affecting the retirement preparation. The results revealed that teachers in Trang Province mostly obtained a high level of retirement preparation. By analyzing each aspect, teachers in Trang Province rated mental preparation as their first priority, followed by the preparation of their physical, their housing, their hobbies, their finances, and their social participation, respectively. By investigating the demographic factors, the results showed that teachers in Trang Province who have differences in age, marital status, monthly income, and the number of children demonstrate different retirement preparation with statistical significance at the 05 level. Furthermore, this study discovered that age was the factor influencing the retirement preparation of teachers in Trang Province with a statistical significance at the 05 level.